2014
DOI: 10.1371/journal.pone.0085723
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Uncertainties in Exposure Assessment on Estimates of Thyroid Cancer Risk among Ukrainian Children and Adolescents Exposed from the Chernobyl Accident

Abstract: The 1986 accident at the Chernobyl nuclear power plant remains the most serious nuclear accident in history, and excess thyroid cancers, particularly among those exposed to releases of iodine-131 remain the best-documented sequelae. Failure to take dose-measurement error into account can lead to bias in assessments of dose-response slope. Although risks in the Ukrainian-US thyroid screening study have been previously evaluated, errors in dose assessments have not been addressed hitherto. Dose-response patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…The current state-of-the-art approach in dosimetry is to document sources and quality of all input data, to establish a dosimetry error structure and to characterize each parameter used in dose calculations as a source of shared or unshared error (5, 6). These data may then be used in a probabilistic dose calculation to generate multiple sets of dose estimates for the entire study population, so that dose-response analyses can be performed using multiple sets of doses (79). …”
Section: Introductionmentioning
confidence: 99%
“…The current state-of-the-art approach in dosimetry is to document sources and quality of all input data, to establish a dosimetry error structure and to characterize each parameter used in dose calculations as a source of shared or unshared error (5, 6). These data may then be used in a probabilistic dose calculation to generate multiple sets of dose estimates for the entire study population, so that dose-response analyses can be performed using multiple sets of doses (79). …”
Section: Introductionmentioning
confidence: 99%
“…The results from GAM models applied to relevant subcohorts are compatible with [6, 11, 13, 15, 34, 35]. They are higher than extrapolations from [1, 36, 37], which concerned higher dose ranges.…”
Section: Discussionmentioning
confidence: 52%
“…Additional file 1: Table S9 shows some results from [1, 6, 7, 11, 13, 15, 3437]. In each case, an appropriate subcohort of the female incidence data was analysed for comparison, using the simplest quasipoisson dose model Q2d and the preferred quasi model for the subcohort, chosen to approximate the dose and agex range in the study, or with mean dose close to that at which risk was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The cohorts have undergone periodic standardized screening for thyroid cancer and nonmalignant diseases of the thyroid. The Ukranian [30][31][32] and Belarusian 33 studies have shown a significantly increased risk of thyroid cancer which was similar in magnitude to the risk associated with external radiation exposure. 4,28 Evidence from other smaller population-based case-control studies confirms a causal relationship between the observed increase in thyroid cancer risk and exposure to 131 I from the Chernobyl fall out.…”
Section: Thyroid Cancer and Other Thyroid Diseasesmentioning
confidence: 78%